Hybrid Strategies for Problems of Shifting Cultivation - Dr. Suraj Bhan (Journal of Soil and Water Conservation, 2022)
As cautioned by Barthakur (1986) and many others working in the areas of shifting cultivation, the problem being a mosaic of complexity, there cannot be a single and simple answer for replacement of shifting cultivation. The problem of jhum requires multidimensional approach. In recent years there have been several scientific innovations based on field researches and trials. At the same time, there have also been several indigenous innovations by the shifting cultivators themselves in response to growing challenges of jhumming. Both these scientific and indigenous innovations elaborately brought out are reflected hereunder for the benefit of both the policy makes and the farmers. Blending of both the scientific and indigenous innovations is looked upon to offer new opportunities and hope for answers to growing problems of shifting cultivation.